История государства Российского: Жизнеописания : XX век (сост.: С. Н. Синегубов, А. В. Шевцов, П. Л. Вахтина) - Синегубов С. Н. (2000)
Экземпляры: ЦБ (2002) / Инвентарный номер: 35574 / Цена: 106.10 / Сис.шифр: 63.3(2) / Авт.знак: И 90 / ГРНТИ: 03 / ББК: 63.3(2)